Effects of mycophenolic acid on human immunodeficiency virus infection in vitro and in vivo - Chapuis, Aude G.; Paolo Rizzardi, G.; D'Agostino, Claudia; Attinger, Antoine; Knabenhans, Christian; Fleury, Sylvain; Acha-Orbea, Hans; Pantaleo, Giuseppe (Nature medicine, 2000)
Mycophenolic acid, a selective inhibitor of the de novo synthesis of guanosine nucleotides in T and B lymphocytes, has been proposed to inhibit human immunodeficiency virus (HIV) replication in vitro by depleting the substrate (guanosine nucleotides) for reverse transcriptase. Here we show that mycophenolic acid induced apoptosis and cell death in a large proportion of activated CD4 + T cells, thus indicating that it may inhibit HIV infection in vitro by both virological mechanisms and immunological mechanisms (depletion of the pool of activated CD4 + T lymphocytes). Administration of mycophenolate mophetil, the ester derivate of mycophenolic acid, to HIV-infected subjects treated with anti-retroviral therapy and with undetectable viremia resulted in the reduction of the number of dividing CD4 + and CD8 + T cells and in the inhibition of virus isolation from purified CD4 + T-cell populations. Based on these results, the potential use of mycophenolate mophetil in the treatment of HIV infection deserves further investigation in controlled clinical trials.